Center for Research on Social Reality (Spain) Survey, April 1992: Justice and Civic Rights ([Verlag nicht ermittelbar], 1993)
This data collection is part of a continuing series of semi-monthly surveys of individuals in Spain. Each survey consists of three sections. The first section collects information on respondents' attitudes regarding personal and national issues. This section includes questions on level of life satisfaction and frequency of relationships, as well as a rating of the importance of national issues. The second section varies according to the monthly topic, with this survey's topic focusing on justice and civic rights. Among the issues investigated are the respondent's personal experience with lawyers and police, evaluation of Spanish prisons and treatment accorded to those in prison, attitudes toward the death penalty, evaluation of the Spanish penal code and the "Corcuera Law," evaluation of government policy with respect to the administration of justice, and perceived image of judicial institutions and justice professionals. The third section collects demographic data such as sex, age, religion, income, and place of residence.